Self-Control and Social Bonds: A Combined Control Perspective on Deviance - Longshore, Douglas; Chang, Eunice; Hsieh, Shih-chao; Messina, Nena (Crime & delinquency, 2004)
With longitudinal data from a sample of adult male drug offenders, this study tested 4 aspects of social bonding (attachment, involvement, religious commitment, and moral belief) and association with substance-using peers as outcomes of low self-control and as mediators of the relationship between low self-control and drug use. Low self-control was negatively related to social bonds and positively related to drug use and association with substance-using peers. The relationship between low self-control and drug use was fully mediated by moral belief and association with substance-using peers. These results support the utility of integrating self-control and social bonding perspectives on deviance. [ABSTRACT FROM AUTHOR]